Depression Leads to Physical Inactivity in Patients with Beta-Thalassemia Major - Faza Nurul Wardhani; Susanti Dharmmika; Hilmi Sulaiman Rathomi (Global Medical & Health Communication (GMHC), 2021)
Beta-thalassemia major (BTM) is difficult to treat chronic disease, causing physical and psychological burdens for the patient. Several studies have confirmed a decrease in physical activity and depression in thalassemia patients, but limited studies examine the relationship between these two conditions. This study aims to analyze the relationship between depression and physical activity in BTM patients in Bandung city. It was analytical observational research with a cross-sectional design. Data were collected during September–December 2018 by interviewing 65 patients selected by simple random sampling from 300 thalassemia patients registered at the Association of Parents with Thalassemia Indonesia/Perhimpunan Orangtua Penderita Thalassemia Indonesia (POPTI) Bandung city. The instruments used were the Global Physical Activity Questionnaire (GPAQ) to measure physical activity and the Beck Depression Inventory (BDI) to assess depressive symptoms. Data were analyzed by chi-square test using SPSS for Windows ver. 23.0. The results showed that most BTM patients in Bandung city were depressed (52%) and had low physical activity levels (65%). Furthermore, there was a statistically significant relationship between depression and physical activity in thalassemia patients in Bandung city (p=0.04, p<0.05). Therefore, it can be concluded that BTM patients in Bandung city with depression have lower physical activity. DEPRESI BERDAMPAK PADA AKTIVITAS FISIK YANG RENDAH PADA PASIEN TALASEMIA BETA MAYORTalasemia beta mayor merupakan penyakit kronis yang sulit disembuhkan sehingga menimbulkan beban fisik dan psikologis bagi pasien. Beberapa penelitian telah mengonfirmasi penurunan aktivitas fisik dan depresi pada pasien talasemia, namun studi yang mengkaji hubungan antara kedua kondisi ini masih terbatas jumlahnya. Penelitian ini bertujuan menganalisis hubungan antara kondisi depresi dan tingkat aktivitas fisik pada penderita talasemia beta mayor di Kota Bandung. Desain penelitian bersifat observasional analitik dengan rancangan potong lintang. Pengambilan data dilakukan selama September–Desember 2018 dengan mewawancarai 65 pasien yang dipilih secara simple random sampling dari 300 pasien talasemia yang terdaftar di Perhimpunan Orangtua Penderita Thalassemia Indonesia (POPTI) Kota Bandung. Instrumen yang digunakan adalah Global Physical Activity Questionnaire (GPAQ) untuk mengukur aktivitas fisik dan Beck Depression Inventory (BDI) untuk menilai gejala depresi. Data dianalisis dengan uji chi-square menggunakan SPSS for Windows ver. 23.0. Hasil penelitian menunjukkan mayoritas penderita talasemia beta mayor di Kota Bandung mengalami depresi (52%) dan memiliki tingkat aktivitas fisik rendah (65%). Selanjutnya, terdapat hubungan bermakna secara statistik antara depresi dan aktivitas fisik pada penderita talasemia di Kota Bandung (p=0,04; p<0,05). Oleh karena itu, dapat disimpulkan bahwa penderita talasemia beta mayor di Kota Bandung yang mengalami depresi memiliki aktivitas fisik yang lebih rendah.